ANALYSIS OF SIMULATION RESULTS OF CET- OPERATIONS BASED ON ELEMENTARY FUNCTIONS OF INFORMATION-DRIVEN OPERATIONS - Rudnytskyi, V. M.; Tarasenko, Ya. V.; Lada, N. V.; Babenko, V. H.; Pidlasyi, D. A. (Systems and Technologies, 2025)
The article considers the currently relevant task of synthesizing CET operations based on elementary functions of infor- mation-driven operations. The work is devoted to reducing the complexity of generating the maximum number of CET operations based on elementary functions of information-driven operations for low-resource stream ciphers. The work involved modelling CET-operations and obtaining four subgroups of 10 symmetric operations. Any of the subgroups can be used to construct 48 CET-operations that include all 10 operations of that subgroup. An analysis of a computational experiment on modelling CET-operations based on elementary information-driven operations was conducted. The absence of intersection among the synthesized sets of CET-operations was established, based on modifications of CET-operations from different subgroups. Based on the selection of four CET-operations (one from each group), it is possible to synthesize a complete group of CET-operations based on elementary information-driven functions. Such a group includes 192 operations. The paper presents a group of ele- mentary functions of information-driven operations and a subset of symmetric CET-operations based on elementary functions of information-driven operations. The requirements for selecting a base group for constructing a method for synthesizing CET- operations based on elementary functions of information-driven operations are described. The conditions for considering the requirements for CET-operations of the base group are presented. Based on the results of a computational experiment, a method for selecting basic groups of symmetric CET-operations has been developed, which makes it possible to reduce the complexity of generating the maximum number of CET-operations based on elementary information-driven operations for low-resource stream ciphers. The developed method can be applied in low-resource telecommunication systems of both mobile and stationary types. The prospect of further research in this area is the construction of low-resource systems for cryptographic information transformation using CET-operations based on elementary functions of information-driven operations.